THE ROLE OF TECHNOLOGY IN EDUCATION - Asliddinov Shahobiddin Qahramon o‘g‘li (TADQIQOTLAR, 2026)
Abstract. This article discusses the importance of modern technologies in the educational process and their impact on improving the quality of teaching and learning. The study analyzes the role of digital tools, online platforms, multimedia resources, and interactive teaching methods in developing students’ knowledge, independent learning skills, and motivation. Special attention is paid to the use of technology in English language teaching at vocational schools. The article also highlights the advantages and challenges of technology-based education and provides recommendations for effective implementation in classrooms.